Komunikasi Organisasi pada Kemitraan Badan Permusyawaratan Desa dengan Kepala Desa dalam Musyawarah Pembangunan di Ponggang Kecamatan Serangpanjang Kabupaten Subang - Dwinarko; Tabrani Sjahfrizal; Pagi Muhamad (Syntax Corporation, 2023)
The Village Consultative Body (BPD) as a working partner of the village chief has the function of supervising village development, setting budget plans together with the village chief, and receiving community aspirations to support sustainable village development. This partnership is constructed through the perception of organizational communication integrated during the village development planning meeting (musrembang) led by the BPD and the village chief. The aim of this research is to understand the organizational communication of the partnership between the Village Consultative Body (BPD) and the Village Chief in the development deliberations in Ponggang Village, Serangpanjang Sub-district, Subang Regency. This research adopts a qualitative descriptive method by analyzing the research results narratively. The narrative is based on the premise that people understand and give meaning to their lives through the stories they tell, using narration to structure and order life experiences. Through the use of storytelling, individuals explain and give significance or meaning to their lives. The qualitative approach enables the selection and interviewing of participants who have actual experiences related to the phenomenon that influences managers. Descriptive analysis techniques are employed in this research by providing detailed descriptions of the partnership between the village consultative body and the village chief in Ponggang. It presents data on the types and frequencies of communication that occur, the communication channels used, and the dominant language in the development deliberation process. The research findings indicate that the partnership takes the form of communication models and patterns among individuals involved in the village-level development planning process, starting from the hamlet level, which is then discussed and implemented at the village level before being further discussed at the sub-district level. The process follows a bottom-up planning pattern. The urgency of this research lies in understanding the partnership's role in prioritizing development through organizational communication in the planning, supervision, and implementation of development budgets.